Spatially resolved quantification of ruthenium oxide phase in a direct methanol fuel cell operated under normal and fuel starved conditions. (1st March 2019) - Dixon, D.; Schoekel, A.; Roth, C.
Abstract: In operando Ru K edge X-ray absorption spectra were recorded at various cell voltages from specific regions of a direct methanol fuel cell (DMFC), such as methanol inlet, outlet and middle regions. From the linear combination fitting analysis, it was found that 50% of the Ru in the pristine Pt/Ru catalyst is in an oxidized form that matches with hydrated ruthenium oxide (RuO2 ·xH2 O). During the DMFC cycling, fraction of this oxide phase gets reduced and forms metallic Ru. Furthermore, it is observed that under normal DMFC operation at various cell voltages relatively a higher amount of RuO2 phase is present at the methanol inlet compared to the methanol outlet. This difference in the amount of RuO2 phase observed translates into inhomogeneous distribution of potential/current within a single cell. The amount of RuO2 phase increased further when the DMFC was subjected to fuel starvation conditions (very high anode potential). Again compared to the methanol outlet region, a higher amount of RuO2 phase was found at the methanol inlet. As RuO2 is more prone to dissolution compared to metallic Ru, it can be concluded that methanol inlet region is more prone to Ru dissolution compared to methanol outlet region. Highlights: RuO2 ·xH2 O phase found throughout the DMFC cycling. Amount of RuO2 ·xH2 O depends on the methanol concentration. The highest amount of RuO2 ·xH2 O found at methanol inlet. Fuel starvation increases the RuO2 ·xH2 O formation. Degradation begins from the more active region like methanol inlet.